Comparison of different methods for debris-flow run-out analyses. Insights from the case of Nus (Valle D’Aosta, Italy) - Carlo Esposito, Gabriele Scarascia Mugnozza, Vittorio Chiessi, Renato Ventura (Journal of Mediterranean Earth Sciences, 2014)
The presented study compares some methods for assessing potential debris-flow paths (and, thus, related spatial hazard) on Alpine alluvial fans in order to evaluate their potential applications. The proposed methods range from empirical to numerical approaches. In particular, the different techniques were used to back-analyse a debris-flow event; their reliability was then assessed by comparing the results with the actual mapped effects of the reference event. The investigated area is located in the western Alpine arc, in the municipality of Nus (Aosta, Italy), which was hit by a major flood on October 2000. Slope phenomena were dominantly of the debris-flow type and affected a wide portion of Nus, which lies on an alluvial fan in the catchment area of the St. Barthélemy river. The main effects of the debris-flow (in terms of invaded areas, erosional and depositional zones) were surveyed and mapped. Such an activity, together with the availability of detailed maps of the event produced by Civil Protection authorities, allowed us to calibrate the input parameters of each adopted methodology. Not much confidence should be put in the results of empirical methodologies as they can be significantly dependent on hardly determinable input parameters, or underestimate the level of hazard and be excessively dependent on previous phenomena. The comprehensive hydraulic methodology produced more reliable results, even if the quality and quantity of data required make this methodology applicable to a limited number of cases. Preference should thus be given to a step-by-step approach which discriminates the fans with a high level of hazard (requiring comprehensive modelling) from those where simplified modelling might be justified. The alternative approach proposed in this study is a volumetric method, which does not need very sophisticated data and takes into account the actual topographic surface and slope gradient. However, crucial to this approach is an adequate estimation of the magnitude of the expected event. Finally, due to its reliability, the hydraulic method was used to perform a forward modeling of event scenario for similar events in the current topographic setting, as modified by the 2000 event. References Armanini A. 1997. Previsione e prevenzione del rischio da colata di detriti. In: Atti del Convegno dei Lincei. Il rischio idrogeologico e la difesa del suolo, Rome, Italy, pp 13-44 Aulitzky H. 1980. Preliminary two-fold Classification of Torrents – Int. Symp InterPraevent 1980, Bad Ischl, Austria 4: 285-309 Berti M., Simoni A. 2007. Prediction of debris flow inundation areas using empirical mobility relationships. Geomorphology 90: 144-161 Bottino G., Crivellari R., Mandrone G. 1996. Eventi pluviometrici critici e dissesti: individuazione delle soglie d’innesco delle colate detritiche nell’anfiteatro morenico di Ivrea. La prevenzione delle catastrofi idrogeologiche: il contributo alla ricerca scientifica 2: 201-210 Ceriani M., Fossati D., Quattrini S. 1998. Valutazione della pericolosità geologica sulle conoidi. Professione Geologo 6: 23-31 COE 1990. HEC-1 Manual COE 1997. Technical Engineering and Design Guide, N. 19 Costa J.C. 1984. Physical Geomorphology of Debris Flows. In: Costa JE, Fleisher PJ (eds) Developments and Application of Geomorphology, Springer-Verlag, Berlin Heidelberg, pp 268- 315 Costa J.C. 1988. Rheologic, geomorphic and sedimentologic differentiation of water floods, hyperconcentrated flows, and debris flows. In: Baker VR, Kochnel PC, Patton PC (eds) Flood Geomorphology, John Wiley & Sons, New York, pp 113-122 Fleming R.W., Ellen S.D., Algus M.A. 1989. Transformation of dilative and contractive landslides debris into debris flows: An example from Marin County, California. Eng Geol 27: 201-223 Gianotti F., Notarpietro S. 2001. Studio sui fenomeni franosi che hanno interessato il territorio comunale di Nus durante l’evento alluvionale del 15.10.2000 ai fini della definizione della loro pericolosità e dei possibili interventi di sistemazione. Unpublished technical report. Hampel R. 1977. Geschiebewirtschaft in Widbachen. Wildbach und Lawinenverbau 41: 3-34 Hungr O. 1995. A model for the runout analysis of rapid flow slides, debris flows and avalanches. Can Geotech J 32: 610-623 Hungr O. 1997. Some methods of landslide hazard intensity mapping. In Fell R., Cruden DM (eds) Proc Landslide Risk Workshop. Balkema, Rotterdam, pp 215-226 Iverson R.M. 1997. The physics of debris flows. Rev Geophys 35: 245-296 Iverson R.M., Schilling S.P., Vallance J.V. 1998. Objective delineation of lahar-hazard zones downstream from volcanoes. Bull Geol Soc Am 110: 972-984 Jackson L.E., Kostaschuk R.A., MacDonald G.M. 1987. Identification of debris flow hazard on alluvial fans in the Canadian Rocky Mountains. Geol Soc Am Rev Eng Geol 7: 115-124 Johnson A.M. 1984. Debris Flows. In: Brundsen D, Prior DB (eds) Slope Instability. Wiley, New York, pp 257-361 Seong K (2002) A study on the effective hydraulic conductivity of an anisotropie porous medium. J Mech Sci Tech 16: 959-965 Lebourg T., Riss J., Fabre R., Clement B. 2003. Morphological Characteristics of till formation in relation with mechanical parameters. Math Geol 35: 835-852 Murray R.S. 1983. Statistics, 2nd edn. McGraw-Hill Nash E.J. 1960. A unit hydrograph study, with particular reference to British catchments. Proc Inst Civ Eng 17: 249–282 O’Brien J.S., Julien P.Y. 1985. Physical processes of hyperconcentrated sediment flows. Proc ASCE Speciality conf on the delineation of Landslides, Floods and Debris Flow hazard in Utah. Utah water research laboratory series UWRL/g 85-03 260-279 O’Brien J.S., Julien P.Y., Fullerton W.T. 1993. Two-dimensional water flood and mudflow simulation. J Hydraulic Engineering, 119, 244-261. O’Brien J.S. 2001. Flo-2d Users Manual Pierson T.C., Costa J.E. 1987. A rheologic classification of subaerial sediment-water flows. In: Costa JC, Wieczoreck G (eds) Debris flows/avalanches process, recognition, and mitigation. Rev Eng Geol 7: 1-12. Razay A.H., Warwick W. 1997. ArcView GIS/Avenue programmers reference: class hierarchy quick reference and 101+ scripts, 2nd edn., OnWord Press, Santa Fe Rickenmann D., Zimmermann M. 1993. The 1987 debris flows in Switzerland: documentation and analysis. Geomorphol 8: 175-189 Savage S.B. 1998. Analyses of slow high-concentration flows of granular materials. J Fluid Mech 377: 1-26 Schilling S.P. 1998. LAHARZ: GIS programs for automated mapping of Lahar-Inundation Hazard Zones. U.S. Geological Survey Open –File Report 98-638: 1-84 Syanozhetsky T.G.V., Beruchashvili G.M., Kereselidze N.B. 1973. Hydraulics of rapid turbulent and quasilaminar (structural) mudstreams in deformed bed with abrupt slopes. In Proc Istanbul Conference of the International Association of Hydrological Scientists, 1, S, pp 507–515 Takahashi T. 1991. Debris flows. IAHR Monograph, Balkema, Rotterdam Tomasetti L., Zonta M.F., Marchelli L., Pallaveri T. 2004. Hydrogeological hazard: the experience of the autonomous Province of Trento in hazard detection and management on urbanised alluvial fan. Internationales Symposion INTERPRAEVENT 2004 – RIVA / TRIENT. IX, pp 262-273 Ya-Lun C. 1969. Statistical Analysis, 2nd edn. Holt, Rinehart and Winston, New York Zeller M., Fullerton W.T. 1983. A theoretically-derived sediment transport equation for sandbed channels in arid regions. In: Li RM and Lagasse FP (eds) Proc of the D. B. Simons Symposium on Erosion and Sedimentation, Colorado State University and ASCE, pp 1134-1148